Contemporary hermeneutics and the interpretation of media texts in the digital age - Abduganieva, Djamila (The Lingua Spectrum, 2025)
This article explores the theoretical and methodological foundations for applying hermeneutics to the analysis of media texts in the context of digital communication. Building on the philosophical frameworks of Hans-Georg Gadamer and Paul Ricoeur, hermeneutics is presented as a universal theory of understanding that emphasizes the historicity of interpretation, the mediating role of language, and the openness of texts to multiple meanings. The paper then examines developments in linguistic hermeneutics, which highlight the contextual nature of meaning, the importance of the reader’s horizon, and intercultural dimensions of understanding. Particular attention is paid to the integration of hermeneutics and discourse analysis in media studies, where media texts are treated as practices of constructing social meanings and power relations. A separate section discusses digital hermeneutics, focusing on how platforms, algorithms and large-scale computational methods (corpus approaches, distant reading) reshape interpretive regimes. The article concludes that a hermeneutic perspective enables researchers to view media not merely as channels of information transfer, but as interpretive spaces where tradition, technology and individual horizons of understanding intersect, opening new possibilities for comprehensive analysis of news, political and multimodal discourses.